3D Elbow Kinematics with Monoplanar Fluoroscopy: In Silico Evaluation. (21st December 2009) - Tersi Tersi, L. L.; Fantozzi Fantozzi, S. S.; Stagni Stagni, R. R.
Abstract : An in-silico assessment of the performance of 3D video-fluoroscopy for the analysis of the kinematics of long bones is proposed. A reliable knowledge of in-vivo joints kinematics in physiological conditions is fundamental in the clinical field. 3D video-fluoroscopy theoretically permits a mm/deg level of accuracy in joint motion analysis, but the optimization algorithm for the pose estimation is highly dependent on the geometry of the bone segment analyzed. An automated technique based on distance maps and tangency condition was applied to the elbow bones. The convergence domain was explored to quantify and optimize measurement accuracy in terms of bias and precision. By conditioning the optimization algorithm using simple image features, the estimation error had small dispersion (interquartile range within 0.5 and 0.025 mm/deg for out-of-plane and in-plane pose parameters, resp.), but with occasional bias and outliers. 3D video-fluoroscopy produced promising results for the elbow joint, but further in-vitro validation studies should be carried out.